PREVALENCE AND GENOTYPING OF HEPATITIS C VIRUS IN HEMODIALYSIS PATIENTS AND EVALUATION OF HCV-CORE ANTIGEN TEST IN SCREENING PATIENTS FOR DIALYSIS IN SANA'A CITY, YEMEN - Hanash, Samira H; Al-Shamahy, Hassan A.; Bamshmous, Mohammed Hussein Saleh (Universal Journal of Pharmaceutical Research, 2019)
Objective: Hepatitis C virus infection is a constant worldwide public health concern. The prevalence of HCV infection is higher in patients on chronic haemodialysis (HD) than in the general population. Despite the control of blood products, hepatitis C virus transmission is still being observed among patients undergoing dialysis. Detection systems for serum HCV antibodies are insensitive in the acute phase because of the long serological window. Direct detection of HCV depends on PCR test but this test is not suitable for routine screening. The objective of this study was to determine prevalence of HCV, genotyping and if HCV core antigen test could be a better alternative to NAT techniques for the diagnosis of HCV infection during the window period and whether the sensitivity for antibody detection is preserved. Methods: Current study includes screening of 159 patients on long-term dialysis by HVC antibodies test, PCR HCV-RNA and HCV core antigen test by commercial tests. Results: The prevalence of HCV was 10.7% (17 patients) and genotype 4 was the most common one (64.7%). The sensitivity of HCV core antigen test was 94.1%, the specificity 100%, the positive predictive power 100%, and the negative predictive power 97.9%. In conclusions; patients on maintenance HD in Yemen have a high prevalence of HCV infection comparing with general population; and genotype 4 is predominant. Conclusion: The performance of serological detection of HCV core antigen was better than that of HCV antibodies test and may be an alternative to nucleic acid amplification technology (NAT) for routine monitoring of patients on chronic dialysis. Peer Review History: Received 6 February 2019; Revised 12 March; Accepted 30 April; Available online 15 May 2019 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewer(s) detail: Dr. O.J Owolabi , University of Benin, Nigeria, owolabi@uniben.edu Dr. Dalia Kamal Zaffar Ali , Modern University for technology and information, Egypt, dr.moda88@gmail.com